HUBUNGAN ANTARA PERTUMBUHAN EKONOMI DAN PENGANGGURAN MENURUT PERSPEKTIF ISLAM - Deis Mahadita; Laura Nur Haliza; Muhammad Khobib Mustafa; Rachmadhianing Putri; Amalia Nuril Hidayati (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Abstrak. This study aims to examine the relationship between economic growth and unemployment from an Islamic perspective. In conventional economics, economics growth is often used as the main indicator of welfare, but it is not always directly correlated with a decrease in unemployment. In the Islamic perspective, economic growth is not only seen from a quantitative perspective, but also from moral values, distribution of justice, and holistic welfare of the people, both in this world and the hereafter. Through a literature approach, the results of this study found that Islam provides solutions to unemployment through the principle of justice in the distribution of wealth, encouragement of entrepreneurship, state responsibility in providing employment, and economic system free from usury. Keywords: Economic Growth, Unemployment, Islamic Economy.